Pharmacoeconomic analysis by the cost-minimization method of fluconazole drugs recommended for use in candidiosis - O. V. Tkachova; L. V. Iakovlieva; T. I. Sheptak (The State Expert Center of the Ministry of Health of Ukraine, 2020)
Candidiasis is a group of fungal diseases of the skin, mucous membranes and internal organs caused by fungi of the genus Candida. Candidiasis treatment is mainly carried out with antifungal agents for systemic use. Fluconazole preparations, which have proven clinical efficacy and safety, and are also most often used in Ukraine, are presented in the largest number of TN in the pharmaceutical market. The aim of the work is to analyze cost minimization when using fluconazole preparations for pharmacotherapy of three different pharmacotherapy schemes for candidiasis. The analysis of minimizing the costs of fluconazole preparations was carried out using the retail cost of medicines according to the Morion company Pharmexplorer analytical market research system (as of February 2019). In the process of calculating the cost of the course of treatment of patients with candidiasis, fluconazole preparations used for pharmacotherapy of 1) vaginal candidiasis were used; 2) dermatomycosis, atrophic candidiasis of the mucous membranes, oropharyngeal candidiasis; 3) candidiasis of the esophagus, candiduria. The study evaluated only the direct costs of treating patients with candidiasis with fluconazole preparations. Calculation of the cost of pharmacotherapy with fluconazole was carried out taking into account the price per package of drugs, the daily dose of drugs with the determination of the cost of one unit (tablets, capsules), one day of treatment and the course of treatment. Based on the results obtained, using the pharmacoeconomic method of «cost minimization», the least costly drugs were selected for the course of treatment with fluconazole. The calculation results showed that the minimum direct costs for the course of pharmacotherapy of the vaginal candidiasis are 9.88 UAH; the minimum direct costs for the treatment of dermatomycoses, atrophic candidiasis of the mucous membranes, oropharyngeal candidiasis are UAH 26.01, and for the treatment of candidiasis of the esophagus and candiduria - UAH 50.28. In a difficult socio-economic situation in Ukraine, the use of the least expensive representatives of antifungal drugs for systemic use is economically feasible. The results of this study will allow the doctor or pharmacist to choose fluconazole preparations in various doses and dosage forms for patients with low solvency.